2018
DOI: 10.3329/ralf.v5i1.36552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different parameters in relation to repeat breeding of cows at the Coastal areas of Bangladesh

Abstract: The aim of this study was to evaluate the presumptive factors might be responsible for repeat breeding syndrome of cows in Bangladesh. The study was conducted in different villages around the Faculty of Animal Science and Veterinary Medicine, Patuakhali Science and Technology University, Outer campus, Barisal during the period from July to September 2017. A total of 100 repeat breeder cows were evaluated considering different presumptive influencing factors such as breed, age, parity, body condition score (BCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
1
2
0
1
Order By: Relevance
“…Overall, 70% of dairy animals suffered from repeat breeding problems followed by 25% repeat breeding with anestrous and only 5% animals with repeat breeding and frequent vaginal discharges (Table 1). Similar findings were also reported by Matubber et al, (2018) who found that 73.5% dairy and animals suffered from repeat breeding problem. Multiple factors such as irregular deworming and vaccination, deficiency of mineral, hormonal imbalance, failure of proper heat detection, etc., generally responsible for the incidence of repeat breeding in dairy animals.…”
Section: Breeding Management Practicessupporting
confidence: 90%
“…Overall, 70% of dairy animals suffered from repeat breeding problems followed by 25% repeat breeding with anestrous and only 5% animals with repeat breeding and frequent vaginal discharges (Table 1). Similar findings were also reported by Matubber et al, (2018) who found that 73.5% dairy and animals suffered from repeat breeding problem. Multiple factors such as irregular deworming and vaccination, deficiency of mineral, hormonal imbalance, failure of proper heat detection, etc., generally responsible for the incidence of repeat breeding in dairy animals.…”
Section: Breeding Management Practicessupporting
confidence: 90%
“…Kejadian RB pada sapi disebabkan oleh banyak faktor di antaranya faktor manajemen pemeliharaan, nutrisi, infeksi, dan hormonal (Barui et al, 2015;Ramandani dan Nururrozi, 2015;Matubber Matubber et al, 2018). Defisiensi nutrisi telah dilaporkan sebagai faktor utama penyebab gangguan reproduksi pada sapi perah (Kumar, 2014;Barui et al, 2015;Ahmed et al, 2017;Sulieman et al, 2017), dan kerbau (Akhtar et al, 2014;Saraswat dan Purohit, 2016).…”
Section: Pendahuluanunclassified
“…age, body condition score, season, parity, lactation stage, milk yield, breed, nutritional management, bull factor, failure to fertilization, and early embryonic death (Nath et al 2014;Singh et al 2008;Saraswat and Purohit 2016;Washaya et al 2019). Some reports consider the degree of RB of dairy cows in speci c regions and fewer repeat breeder cases in Bangladesh but information relating to its prevalence and risk factors for RB is very scanty (Islam et al 2017;Asaduzzaman et al 2016;Matubber et al 2018). Hence, this study was undertaken to envisage the prevalence and potential risk factors associated with RB in dairy cows in selected milk pocket districts of Bangladesh, viz.…”
Section: Introductionmentioning
confidence: 99%